Understanding The Nature of Science (NOS) of In-Service Science Teachers: Instructional Practices and Their Implications on Renewable Energy - Utami, Indri Sari; Rochintaniawati, Diana; Rusdiana, Dadi; Suwarma, Irma Rahma (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2022)
The purpose of this study was to determine the understanding of science teachers about the nature of science (NOS) and its instructional practices and implications for renewable energy. Surveys and interviews were conducted on science teachers and elementary, middle, and high school/vocational school students in this study. The instrument used was adapted from the NOS questionnaire instrument and interview questions Abd-El-Khalick, Bell, and Lederman, then developed and refined according to the respondents to measure NOS understanding and instructional practice. Questions added regarding teaching about renewable energy. This research is a qualitative research conducted online on science teachers in Java, Indonesia. Then the contents of the questionnaire are projected on the NoS understanding rubric which is divided into don't understand the NOS aspect yet, little understanding of the NOS aspect, and know and understand aspects of NOS. While the results of the interviews are presented in a qualitative descriptive manner. The results showed a lack of understanding of science teachers about NOS and its instructional practices. Understanding is still very lacking in the tentative aspects, observation and inference, as well as theory and law. The teaching of renewable energy that can train students' NOS which is felt urgent to be taught is also not applied by the teachers in their teaching. Various obstacles were expressed such as immature preparation, limited learning time, and lack of understanding. This resulted in poor implementation of aspects of NoS in classroom learning which had an impact on students' understanding.